Analysis of the Impact of Preoperative Education on Patient Satisfaction and Outcomes in Neurosurgery - Shakya, Bikram; K C, Bidur (Nepal Journal of Neuroscience, 2024)
AbstractBackground:Preoperative education has been increasingly recognized as a vital component in enhancing patient outcomes and satisfaction in surgical care, especially in neurosurgery, where procedures are complex and carry significant risks. This study aims to analyze the impact of preoperative education on patient satisfaction and postoperative outcomes in a tertiary care neurosurgical setting in Nepal, a region with limited healthcare resources.Methods:This prospective, observational cohort study was conducted at the Department of Neurosurgery, Kathmandu Medical College Teaching Hospital, over a 12-month period. A total of 48 adult patients scheduled for elective neurosurgical procedures were enrolled and divided into two groups: the intervention group, which received a structured preoperative education program, and the control group, which received standard preoperative care. The intervention included a one-hour educational session covering surgical procedures, anesthesia, postoperative care, and potential complications, supplemented with visual aids. Patient satisfaction was assessed using a validated questionnaire 48 hours postoperatively, while clinical outcomes such as the length of hospital stay, time to recovery, and postoperative complications were evaluated through medical record reviews. Statistical analyses included chi-square tests, independent t-tests, and logistic regression analysis.Results:Patients in the intervention group reported significantly higher satisfaction scores (8.9 ± 0.8) compared to the control group (7.3 ± 1.2, p < 0.001). They also demonstrated better understanding of their procedures, increased confidence in the medical team, and reduced preoperative anxiety levels. Additionally, the intervention group experienced shorter hospital stays (4.2 ± 1.3 days vs. 5.6 ± 1.8 days, p = 0.01) and faster recovery times (3.5 ± 0.9 days vs. 4.8 ± 1.2 days, p = 0.002). Although the difference in postoperative complication rates was not statistically significant, a lower incidence was observed in the intervention group (8.3% vs. 20.8%, p = 0.20). Multivariate logistic regression identified preoperative education as a significant predictor of high patient satisfaction (OR: 3.5, 95% CI: 1.8-6.7, p < 0.001).Conclusion:Structured preoperative education significantly improves patient satisfaction and clinical outcomes in neurosurgical patients. These findings support the integration of comprehensive educational programs into preoperative care routines, particularly in low-resource settings like Nepal, where informed patient engagement can enhance the quality of care and postoperative recovery. This study contributes to the growing body of evidence advocating for patient-centered approaches in neurosurgery to optimize patient experiences and surgical outcomes.Keywords:Preoperative education, patient satisfaction, neurosurgery, postoperative outcomes, patient-centered care, low-resource settings.